Ergonomic Factors Prevent The Risk Of Musculoskeletal Disorders (MSDS) And Increase Work Productivity - Gempur Santoso (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This article aims to reveal that ergonomic factors can prevent the risk of MSDs, which then increases work productivity optimally. The design of this article is descriptive. Various opinion data are taken from various literature, this is usually called literature study. Data processing was carried out using descriptive analysis. The method for making conclusions is done inductively. Conclusion: First, ergonomic factors as prevention of MSDs, namely individual factors, include: 1) Age, work at a productive age, not when you are already retired; 2) Gender, comply with the NAB threshold value, because for this type of lifting work, men and women have different (NAB) loads; and 3) psychosocial, namely aspects related to one's own psychology and society. The psychological aspect of course comes from within oneself, while the social aspect comes from outside (external). These two aspects are very influential during our growth period in our ability to work. Occupational factors: 1) muscles do not receive static loads repeatedly; 2) workload, avoid working overload and overtime; 3) working period, working for a long time has a long working period, this will lead to aging and weakening of skeletal muscles naturally; 4) work posture, appropriate work posture means that it is not monotonous, there is work relaxation, and the equipment is adapted to anthropometric dimensions of human size; 4) work climate, this is related to temperature, humidity and wind speed, all must be adjusted to NAB; and 5) working time, must have a work rhythm and work 8 hours per day or 40 hours per week. Factors before work/outside of work: 1) do light skeletal muscle stretching before work; 2) exercise once a week. Second, working with MSDs will accelerate total fatigue at work which will reduce work productivity. Suggestion: for companies to pay attention to several ergonomic factors, so that workers do not get tired quickly, so that work productivity can increase optimally.